2019
DOI: 10.1136/bmjebm-2019-111271
|View full text |Cite
|
Sign up to set email alerts
|

HOSPITAL Score, LACE Index and LACE+ Index as predictors of 30-day readmission in patients with heart failure

Abstract: This study aimed to evaluate the accuracy of the HOSPITAL Score (Haemoglobin level at discharge, Oncology at discharge, Sodium level at discharge, Procedure during hospitalization, Index admission, number of hospital admissions, Length of stay) LACE index (Length of stay, Acute/emergent admission, Charlson comorbidy index score, Emerency department visits in previous 6 months) and LACE+ index in predicting 30-day readmission in patients with diastolic dysfunction. Heart failure remains one of the most common h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 18 publications
(26 reference statements)
6
33
0
Order By: Relevance
“…Other studies found that the complication rate of a hospital as well as the readmission of patients represent major influencing factors [38,39]. Ibrahim et al examined the readmission rate of heart failure patients but failed to demonstrate an influence of medical scores on the 30-day readmission rate [39]. Still, medical aspects are likely to have an influence on the hospital choice and should therefore be considered whenever possible.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies found that the complication rate of a hospital as well as the readmission of patients represent major influencing factors [38,39]. Ibrahim et al examined the readmission rate of heart failure patients but failed to demonstrate an influence of medical scores on the 30-day readmission rate [39]. Still, medical aspects are likely to have an influence on the hospital choice and should therefore be considered whenever possible.…”
Section: Discussionmentioning
confidence: 99%
“…Hospital readmissions are a worldwide, major health-care burden, with a negative impact on patient health, public health, and healthcare systems' associated national financial burden. Previous publications describe the heavy toll of hospital (non-surgical) re-admissions while the same researchers and others attempted various strategies for either predicting the risk for readmission and proactively reducing it (albeit with conflicting results) [5][6][7][8][9][10].…”
Section: The Need For Internal Medicine Personalization Hospital Lenmentioning
confidence: 99%
“…11,13,14,15 In one retrospective study that included HFpEF patients, both HOSPITAL and LACE index did not show association with increased readmissions. 16 Very few studies have focused determining the association of the type of heart failure in hospital readmissions. 17 This provides a motivation to explore the types of heart failure and identify their association with hospital readmission.…”
mentioning
confidence: 99%